Pengaruh Nilai Pelanggan terhadap Kepuasan Pelanggan (Studi Kasus di Toko NN Garut) - Hadiyan, Moch Hadiyan Al Gibrani; Yusuf, Ramayani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The growth of business actors in Indonesia, which is currently increasing rapidly, can be a challenge or a threat for other business actors to win the competition in the market. The purpose of this research is to test empirically the effect of customer value on customer satisfaction. The object used is the Garut NN Shoe Store with a sample of 100 customers in the Garut area using a purposive sampling technique. The questionnaire given to each respondent uses a Likert scale measurement. Research using linear regression as a method of data analysis. The results showed that customer value has a positive effect and has a strong relationship to customer satisfaction